Implementasi Kurikulum Pai Dan Sistem Full Day Dalam Pembentukan Nilai Disiplin Dan Tanggung Jawab Siswa SMA: Studi Kasus Di Yayasan Perguruan Istiqomah - Fandina Amelia; Hasrian Rudi Setiawan (EL-EMIR Institute, 2025)
This research aims to analyze the implementation of the Islamic Religious Education (PAI) curriculum in the full day school system as well as its contribution to the formation of student discipline and responsibility. This research uses a qualitative approach with a type of case study at Yayasan Perguruan Istiqomah High School, involving the principal, PAI teachers, students, and parents. Data was collected through observation, interviews, and documentation studies, then analyzed using the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results of the research show that the PAI curriculum is integrated in the full-day system through a combination of academic activities and religious training such as prayer, reciting the Qur'an, mentoring, thematic studies, and extracurricular activities. This process is effective in forming student discipline through regularity of time, compliance with the worship schedule, as well as academic consistency, while fostering a sense of responsibility through active participation in various school programs.